ANALISIS HERMENEUTIK MOTIF GUIRLANDE PADA PELIPIT CANDI-CANDI PENINGGALAN MATARAM KUNO : Hermeneutical Analysis of Garland Motifs in the Spiral Ornamentation of Ancient Mataram Era Temples - Nurulfatmi Amzy; Herliyana Rosalinda; Edo Galasro Limbong (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2024)
The temple is considered as a homage to the gods. As gods reverence, the building is decorated with numerous beautiful motifs. Each decoration presents a value, either symbolic or aesthetic. Some previous studies have only explored the decorative motifs depicted on the roof, body, and base. The temple also consists of a cornice and plinth. They serve as separators between those three main parts of the temple. Some decorative motifs are also depicted on those parts. This essay discusses one of the decorative motifs usually applied on cornices and plinths, namely garland motifs. This research aims to identify various garland motifs in the ancient Mataram temple buildings (8-10C). The method used in this research is Wilhelm Dilthey's hermeneutics. It explains that in empirical data, there are patterns connected. Those patterns give meaning to experience and life. Dilthey's hermeneutics is carried out by looking at those patterns, understanding them, and interpreting their means. This research will reveal the meaning of the elements that form the garland motif. By understanding the interconnectedness of each element's intention, we can also understand the universal value of the garland motif in the temple building.